2005
DOI: 10.1507/endocrj.52.259
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxidative Effect of Fluvastatin in Hyperlipidemic Type 2 Diabetic Patients

Abstract: Abstract. An open-label prospective cross-over trial was performed to evaluate the antioxidative effect of fluvastatin in Japanese type 2 diabetics with hyperlipidemia. The study subjects were 10 patients who were on pravastatin (10 mg/day) or simvastatin (5 mg/day). After at least 12 weeks of continuous pravastatin or simvastatin therapy, the drugs were washed out for 12 weeks and replaced with fluvastatin (30 mg/day), then the treatment was continued for another 12 weeks. Total cholesterol and LDL cholestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 22 publications
(15 reference statements)
1
8
0
Order By: Relevance
“…As discussed more thoroughly in Paper III, the antioxidative capacity of fluvastatin has been reported by others in other model systems, such as human aortic smooth muscle cells [173] and on the plasma lipids of hyperlipidemic subjects [174]. This is proposed to be a consequence of its unique structure compared to other statins, giving it a free radical-scavenging activity against the superoxide anion and hydroxyl radical [175,176] that is independent of its HMG-CoA reductase inhibition capacity [177].…”
Section: Paper Iii: Anti-oxidative Effects Of Statins On Vascularmentioning
confidence: 78%
“…As discussed more thoroughly in Paper III, the antioxidative capacity of fluvastatin has been reported by others in other model systems, such as human aortic smooth muscle cells [173] and on the plasma lipids of hyperlipidemic subjects [174]. This is proposed to be a consequence of its unique structure compared to other statins, giving it a free radical-scavenging activity against the superoxide anion and hydroxyl radical [175,176] that is independent of its HMG-CoA reductase inhibition capacity [177].…”
Section: Paper Iii: Anti-oxidative Effects Of Statins On Vascularmentioning
confidence: 78%
“…As a form of treatment in order to ameliorate the negative effect of oxidative stress, antioxidant therapy is a very promising intervention in minimizing the complications associated with oxidative stress in diabetes mellitus [ 31 , 32 ]. Thus, the present study showed that Vit-C decreased the blood glucose concentration in diabetic rats, and a more significant lowering-effect was recorded when probiotic and Vit-C were co-administered ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Statins have been widely reported on for their antioxidant properties based on assessment of oxidative stress biomarkers in readily accessible fluids such as blood, 17–19 plasma, 20,21 serum, 22 and urine 23,24 . Although thought to reflect generalized oxidative stress status, a study investigating the specific relationship between peripheral (fluid) and tissue levels of oxidative stress demonstrated peripheral levels of oxidative stress biomarkers do not correlate with tissue levels and may not reflect the local oxidative stress status of individual organs 25 .…”
Section: Discussionmentioning
confidence: 99%